Enhancing student engagement in entrepreneurial activities: the case of Iowa State University - Cummings, Carly (Kansas State University, 2016)
Iowa State University’s Agricultural Entrepreneurship Initiative (AgEI) was founded in 2005 from a generous gift given by Roger and Connie Underwood of Ames, IA. The original mission for the initiative was to provide undergraduate students at Iowa State University, specifically in the College of Agriculture and Life Sciences (CALS), with practical business development and entrepreneurial experiences essential for their success in future careers and endeavors. A non-conventional case study structure will walk readers through the history of how the AgEI program came to be and introduce them to the present day, while acknowledging tribulations the program has faced along the way. The purpose of this study is to determine wether the addition of soft skills programming will strengthen the value of the program to Iowa State University CALS students and generate actionable ideas on how to do so. Further analysis will ascertain whether enticing additional participation in the program, while maintaining its original entrepreneurial goals, will allow the AgEI program to grow in value and size. Quantitative, as well as qualitative, means of analysis are utilized to understand the students’ needs for soft skills development and identify skills deemed necessary by entrepreneurs to find success in the marketplace. Results indicate that it is advantageous to add a focus in soft skills development for undergraduate students who have an interest in entrepreneurship and small business development. These skills compliment their technical skills nicely when considering all aspects of creating a successful startup business. By implementing soft skills development programming, the AgEI program will be able to produce more well-rounded individuals and enhance their likelihood to successfully start their own businesses.
Keywords: soft skills; entrepreneurship; agriculture; case study; education